Antioxidants and the risk of sleep disorders: results from NHANES and two-sample Mendelian randomization study - Jiang, Junjie; Li, Dong; Huang, Tao; Huang, Shan; Tan, Hanyu; Xia, Zhongfang (Frontiers in Nutrition, 2024)
Background: Sleep disorders have emerged as a major public health concern. Observational research indicates that antioxidants might mitigate the risk of sleep disturbances, yet the causal relationship remains uncertain. Materials and Methods: This study utilized data from the National Health and Nutrition Examination Survey (NHANES) spanning 2011 to 2018, focusing on adults who reported sleep disorders. The analysis included 25,178 American adults. We examined the association between the Composite Dietary Antioxidant Index (CDAI) and the prevalence of sleep disorders. Additionally, a two-sample Mendelian Randomization analysis was conducted to explore the potential causal link between CDAI and the risk of sleep disorders. Results: Analysis of data from the 2011-2018 NHANES survey revealed a significant negative association between CDAI and sleep disorders (OR = 0.854, 95% CI 0.821-0.888, P < 0.001). A multivariable logistic regression model showed that each unit increase in CDAI corresponded to a 14.6% reduction in sleep disorder risk, exhibiting a nonlinear trend where the risk decreased until reaching the inflection point of -0.134. Additionally, MR analysis demonstrated that genetically determined selenium reduces the risk of OSA (OR = 0.992, 95% CI 0.860–0.989, P = 0.023). Furthermore, vitamin E (γ-tocopherol) and vitamin C were protective against sleep-wake disorders (OR = 0.016, 95% CI 0.001–0.674, P = 0.03) and (OR = 0.049, 95% CI 0.007–0.346, P = 0.002), respectively. Conclusion: Dietary antioxidants may help prevent sleep disorders. However, further studies are required to clarify the pathways through which antioxidants exert this protective effect..